The Role of FNAC in Diagnosis of Breast Disease at Different Ages - 208 Cases (Journal of Bangladesh College of Physicians and Surgeons, 2012)
All breast lesions are not malignant, and all the benign lesions do not progress to cancer; however the accuracy of diagnosis can be increased by a combination of preoperative tests. About 30% of women suffer from breast disease in their lifetime. The main objectives are to explore the role of FNAC in diagnosis of breast disease at different ages. Fine needle aspiration cytology (FNAC) has become a critical component in the investigation of palpable breast masses. Total 208 cases included in this study at Comilla. The data was formulated and analyzed by SPSS-12. 79(37.98%) cases were at the age of 21-30 years and next one was 11-20 years which was 48(23.07%). Among them 40(19.23%) cases were   malignant and 168(80.77%) cases were benign in nature. The incidence of malignancy was increased with relation to age. As the age is more chance of malignancy is more. In benign types fibroadenoma was the common disease then the duct cell carcinoma, fibrocystic change, suppurative   inflammation respectively. The findings were 43.75%, 19.23%, 18.27% and 8.65%.In conclusion, fine needle aspiration cytology, for diagnosis of breast lump can reduce the number of open biopsy and   surgery. DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12462 J Bangladesh Coll Phys Surg 2012; 30: 137-140